If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+4)-16=2(2x+5)+3
We move all terms to the left:
3(x+4)-16-(2(2x+5)+3)=0
We multiply parentheses
3x-(2(2x+5)+3)+12-16=0
We calculate terms in parentheses: -(2(2x+5)+3), so:We add all the numbers together, and all the variables
2(2x+5)+3
We multiply parentheses
4x+10+3
We add all the numbers together, and all the variables
4x+13
Back to the equation:
-(4x+13)
3x-(4x+13)-4=0
We get rid of parentheses
3x-4x-13-4=0
We add all the numbers together, and all the variables
-1x-17=0
We move all terms containing x to the left, all other terms to the right
-x=17
x=17/-1
x=-17
| p-22/9=7 | | 12x=x-2/16 | | 90^x/4=1,000,000 | | -4(u-1)=-4(u+4) | | 8-2p=14 | | 37=b/8+35 | | 6(x-6)=6(x-7) | | 7(-7+5x)=266 | | 4+(55*3)-(16*3)2=h | | 2(c-48)=34 | | 1010x+270=15x+10 | | 9x2-490x+2000=0 | | x+2=-3x+38 | | X+3x+x-14=76 | | 2x-6=3+3x | | 6x+101=10x-7 | | 48=-7c-9c | | 8(c+7)=8(c-9) | | 2=-2n+6 | | 3w-19=11 | | t=7011*3 | | 3a-5+4(a+2)=10 | | -2(x-5)+3=-4 | | 9(x-7)=3x-33 | | 5x+11/12=60 | | 7w+-12w+-24=11 | | -12+.75x=-6 | | -4x×1=-15 | | 46-6k=4 | | h=2+(50)2-(16*2)2 | | 4.5-j=3.2 | | 7w+12w+24=11 |